2002
DOI: 10.1021/jp013286i
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Triblock Copolymers of Ethylene Oxide and Propylene Oxide at the Air/Water Interface:  The Surface Excess

Abstract: Neutron reflection has been used to measure the surface excesses of two poly(ethylene oxide-b-propylene oxide-b-ethylene oxide) triblock copolymers (EPE) at the air/water interface over a range of bulk solution concentrations. The copolymers, of approximate formulas E23P52E23 and E9P22E9 and have similiar adsorption isotherms in terms of their molar adsorption, though quite different in terms of segmental adsorption. The isotherms have two steps, one at low concentrations leading to a plateau over about two de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
48
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(54 citation statements)
references
References 23 publications
6
48
0
Order By: Relevance
“…Such a hypothesis is in agreement with the results of previous studies that demonstrated the important role of steric repulsion in the interactions between polymer-coated surfaces 64,65 , and in the stability of emulsions 66 and foams 67 in the presence of EO-PO co-polymers.…”
Section: Morphology Of the Films At Toluene-water Interfacesupporting
confidence: 93%
“…Such a hypothesis is in agreement with the results of previous studies that demonstrated the important role of steric repulsion in the interactions between polymer-coated surfaces 64,65 , and in the stability of emulsions 66 and foams 67 in the presence of EO-PO co-polymers.…”
Section: Morphology Of the Films At Toluene-water Interfacesupporting
confidence: 93%
“…Note that the highest concentration employed for all tested PEO surfactant polymers was limited by their water solubility. The surface tension plots are similar to those reported for pure PEO, AB and ABA-type PEO surfactants [20][21][22][23]. The minimum surface tensions in Region I for all tested polymers were similar (63.5-61 dyne/cm) to that of pure PEO, indicating that the decreases in surface tension were primarily dictated by the PEO ligands.…”
Section: Surface Active Properties At the Air/water Interfacesupporting
confidence: 79%
“…The surface properties of some pluronics have been studied in the literature by means of different techniques such as dynamic and equilibrium surface tension, ellipsometry, surface rheology and neutron reflectivity at the air-water and hexane-water interfaces [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Some of these studies show the occurrence of conformational changes within the adsorbed layer of Pluronics at the interface when increasing the amount of adsorbed polymer, suggesting that the conformation of Pluronic molecules changes from a 2D flat conformation to a 3D brush/mushroom one at the interface [16,17,20].…”
Section: Introductionmentioning
confidence: 99%